An evaluative study of portfolio implementation in the Egyptian primary schools - Mohammed Hegazi Abdellatif Abdelmejeed Almaraghy; Abdelrehim Saad Eldin Alhilaly; Ali Ahmed Madkour (Cairo : Mohammed Hegazi Abdellatif Abdelmejeed Almaraghy, 2013)
The current study aimed at evaluating the implementation of EFL portfolio of the third year primary stage pupils. Participants of the study were selected randomly from two government primary schools. Two main instruments were used in this study; a questionnaire to identify EFL teachers' perceptions of portfolio and an observation sheet
Thesis (M.Sc.) - Cairo University - Institute of Educational Studies - Department of Curriculum and Methods of Teaching
Issued also as CD
Keywords: Egyptian primary schools; Evaluation and assessment; Portfolios